The Concept of “Security” in Annual Speeches of the Republic of Poland Ministers of Foreign Affairs after 2001 - Pochyły, Piotr (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2017)
After the WTC attacks in 2001, the international situation and security in the world has changed. The United States and its allies – including Poland – have started a war against global terrorism and got involved in the war in Afghanistan and Iraq. The economic crisis at the end of the first decade of the 21stcentury, the Arab Spring, the rise of the so-called Islamic State, the war in Ukraine and the refugee crisis have affected the state of security in Poland and in Europe. Since 2014 Poland’s foreign ministers have been forced to react to the most difficult geostrategic situation after 1989. The paper analyses the issue of security in the annual speeches of Poland’s for- eign ministers. The research problem is the impact of the international situation on the contents of the ministers’ annual speeches in this regard.

Wraz z zamachami na WTC w 2001 roku sytuacja międzynarodowa i stan bezpieczeństwa na świecie zmieniły się. Stany Zjednoczone wraz z sojusznikami – w tym z Polską, rozpoczęły wojnę ze światowym terroryzmem i zaangażowały się w wojny w Afganistanie i w Iraku. Kryzys ekonomiczny z końca pierwszej dekady XXI w. na świecie, „Arabska Wiosna”, powstanie tzw. Państwa Islamskiego, wojna na Ukrainie i kryzys uchodźczy oddziaływały na stan bezpieczeństwa w Polsce i w Europie. Od 2014 roku polscy ministrowie spraw zagranicznych zmuszeni są reagować na najtrudniejszą sytuację geostrategiczną od 1989 roku. W artykule analizie poddane zostało zagadnienie bezpieczeństwa w exposé ministrów spraw zagranicznych Polski. Problem badawczy to wpływ sytuacji międzynarodowej na treści exposé poszczególnych ministrów w tym aspekcie.
Pojęcie ,,bezpieczeństwo" w exposé ministrów spraw zagranicznych RP po 2001 roku
Keywords: exposé; security; international security; foreign affairs; WTC; exposé; bezpieczeństwo; bezpieczeństwo międzynarodowe; polityka zagraniczna Polski; WTC